A “I FOUND SHIFA IN SURA -AL RAHMAN’’: A PHENOMENOLOGICAL STUDY OF THE HEALING EXPERIENCES FROM PAKISTAN - Rashida Qureshi; Mahrukh Zahoor; Mahwish Zahoor (International Journal of Islamic and Complementary Medicine, 2026)
The purpose of this qualitative study was to explore and understand the healing experience during a seven-day Quranic therapy session in Pakistan, a predominantly Muslim country. Data were collected through in-depth face-to-face interviews and analyzed using Reflexive Thematic Analysis (RTA) combining deductive and inductive approaches. The deductive approach provided a framework for analysis by identifying key categories, while the inductive approach allowed for in-depth exploration of new themes for meaningful interpretation. Three key themes emerged: (1) syifa (healing and restoration) comes from Allah as the Healer; (2) “Indeed, by remembering Allah, hearts find rest”; and (3) “Indeed, with hardship comes ease.” The results of the study indicate that healing is multidimensional as a subjective experience. In a medical context, healing is often associated only with physiological symptoms, but individual experiences demonstrate that healing is not limited to physiological aspects alone. To be holistic, healing must include transformation in the individual’s psychosocial and spiritual aspects. Therefore, it is recommended that the practice of Quranic therapy be recognized as part of a non-pharmacological healing system, and further research is needed to support this.